Foreign Capital and Domestic Productivity in Developing Countries: An Empirical Analysis - Adam, Fadzli (Asian Development Policy Review, 2020)
Foreign direct investment (FDI) has originally been regarded as the navigating force of economic activities and economic growth (EG) worldwide, especially in developing countries. The influence of FDI growth on EG involves the absorptive capacities of developing nations. The benefits of FDI can be maximized by enhanced technology transfers and productivity spillover. In this context, the motivation to conduct the current study was to investigate the impact of FDI on the TFP of developing countries, along with the control variables of human capital (HC) and the political institutional (PI) index. As the current study has been conducted in the context of developing countries, the researcher has collected data from world developing indicator (WDI) including Cambodia, Lebanon, Morocco, Malaysia, Thailand, Bahrain, and Cameroon. The panel data was collected from the aforementioned countries over a time period of 30 years. In order to obtain the results, the data were analyzed using the SYS-GMM estimation technique. The findings of the paper indicate that the lagged FDI has a significant impact on TFP, whereas the lagged FDI has an insignificant impact on TFP. The outcome obtained by the application of the interplay term FDI*HC indicated that FDI alone has no direct impact on TFP; however, the impact of the interaction term FDI*HC is positive on TFP. The result obtained by estimating the two interaction terms FDI*HC and FDI*INT collectively suggested that FDI alone has an insignificant influence on TFP; however, the impact of the interaction term FDI*INT on TFP is positive.